Diagnostic, prognostic and therapeutic role of CD30 in lymphoma. Issue 1 (2nd January 2017) - Pierce, John Matthew R.; Mehta, Amitkumar
ABSTRACT: Introduction : CD30 is a cell surface receptor expressed in classical Hodgkin lymphoma (HL), anaplastic large cell lymphoma (ALCL), and many other lymphomas to a variable degree. It has been identified as an important therapeutic target in lymphoma. Areas covered : CD30 testing is essential in diagnosis of classical HL and ALCL, and expression can also be seen in other lymphoma subtypes. Development of Brentuximab vedotin (BV), an antibody-drug conjugate directed to CD30, has been an important advance in lymphoma treatment. It is approved in treatment of relapsed HL and ALCL, as well as post-transplant maintenance for HL, and has been shown to be effective in other CD30-expressing lymphomas. This review describes the role of CD30 and the use of CD30-targeted agents in HL, ALCL, and other lymphomas, including review of relevant trials of BV. Expert commentary : Recognition of CD30 expression in lymphoma has led to the development of important therapeutic options. Multiple trials are ongoing combining BV with other agents, such as chemotherapy or immunotherapy, to develop more effective regimens. In addition, treatments targeting CD30 in different ways are being developed, such as bispecific antibodies and chimeric antigen receptor (CAR) T-cells.